Development and Validation of the Client‐Reported Quality of Contraceptive Counseling Scale to Measure Quality and Fulfillment of Rights in Family Planning Programs. Issue 2 (23rd May 2019) - Holt, Kelsey; Zavala, Icela; Quintero, Ximena; Hessler, Danielle; Langer, Ana
Abstract: We developed the Quality of Contraceptive Counseling (QCC) Scale to improve measurement of client experiences with providers in the era of rights‐based service delivery. We generated scale items drawing on the previously published QCC Framework and qualitative research on women's preferences for counseling in Mexico, and refined them through cognitive interviews (n = 29) in two Mexican states. The item pool was reduced from 35 to 22 items after pilot testing using exit interviews in San Luis Potosí (n = 257). Exploratory Factor Analysis revealed three underlying dimensions (Information Exchange, Interpersonal Relationship, Disrespect and Abuse); this dimensionality was reproduced in Mexico City (n = 242) using Confirmatory Factor Analysis. Item Response Theory analyses confirmed acceptable item properties in both states, and correlation analyses established convergent, predictive, and divergent validity. The QCC Scale and subscales fill a gap in measurement tools for ensuring high quality of care and fulfillment of human rights in contraceptive services, and should be evaluated and adapted in other contexts.